1996
DOI: 10.1097/00000542-199603000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Lidocaine and Bupivacaine Dose-dependently Attenuate Bronchial Hyperreactivity in Awake Volunteers

Abstract: In awake humans, intravenous lidocaine and bupivacaine both dose-dependently attenuated the hyperreactive response to a nonspecific inhalational challenge with acetylcholine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
8

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 28 publications
0
12
0
8
Order By: Relevance
“…Plasma and interstitial concentrations of local anesthetics ranges from 5–20 µ M after intravenous [38, 39]and epidural [40, 41]injections to 1–10 m M range [42]after local nerve plexus infiltrations (e.g. interscalene or axillary block).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma and interstitial concentrations of local anesthetics ranges from 5–20 µ M after intravenous [38, 39]and epidural [40, 41]injections to 1–10 m M range [42]after local nerve plexus infiltrations (e.g. interscalene or axillary block).…”
Section: Discussionmentioning
confidence: 99%
“…This way, autonomic reflexes such as the coughing reflex or reflex bronchoconstriction can be suppressed with lidocaine plasma concentrations of 1.0-2.0 µg·ml −1 , i.e., far below the toxic threshold of 5.0 µg·ml −1 [76][77][78]. In asthmatic volunteers, intravenous lidocaine doses of 1.0-2.0 mg·kg −1 body weight significantly attenuated histamine-induced bronchoconstriction [65,67].…”
Section: The Effects Of Local Anesthetics On Lung Function and Bronchmentioning
confidence: 99%
“…This effect is comparable to a moderate dose of a β2-adrenergic agonist such as salbutamol, and leads, in combination with salbutamol, to an additive effect [79]. Therefore, in cases of expected airway irritation, prophylactic treatment with lidocaine and a β2-adrenergic agonist can be recommended [72,77]. As well as its use as a prophylactic agent, intravenous administration of lidocaine has been used successfully to treat bronchospasm [69,80].…”
Section: The Effects Of Local Anesthetics On Lung Function and Bronchmentioning
confidence: 99%
“…4e6 Intravenous administration of lidocaine or bupivacaine has been reported to attenuate bronchial hyperreactivity in awake humans. 7 It has been demonstrated that bupivacaine or lidocaine applied topically to the smooth muscle of isolated rat tail arteries can inhibit vascular contraction in response to adrenergic activation. 8 The effect of bupivacaine topically applied to the trachea has not been well explored.…”
Section: Introductionmentioning
confidence: 99%